Pengaruh Profitibalitas, Struktur Modal, dan Ukuran Perusahaan Terhadap Nilai Perusahaan pada Emiten Pertambangan yang Terdaftar di ISSI Periode 2020-2024 - Rolis Rolis; Muhammad Daffa Dhiya’ulhaq; Peny Cahaya Azwari (As-Syirkah: Islamic Economic & Financial Journal, 2026)
This study aims to analyze the influence of profitability, capital structure, and firm size on firm value in the mining sector listed on the Indonesian Sharia Stock Index (ISSI) during the 2020–2024 period. This study uses a quantitative approach with causality research. The sample was determined through purposive sampling and obtained 15 companies from a total population of 63 companies. Data analysis used panel data regression with EViews 12 software. The results show that profitability has a positive and significant effect on firm value. However, capital structure and firm size do not significantly influence firm value. Simultaneously, the three independent variables significantly influence firm value with an F-probability value of 0.008791. The R-squared value of 0.150059 indicates that 15% of the variation in firm value is explained by these three variables, while the remainder is influenced by factors outside the research model.